Canary in the coal mine: Lessons from the Jarrah Forest suggest long-term negative effects of phosphorus fertilizer on biodiverse restoration after surface mining - Daws, Matthew I.; Blackburn, Cameron; Standish, Rachel J.; Tibbett, Mark (Frontiers in Forests and Global Change, 2022)
Despite nutrient enrichment having widely reported negative impacts on biodiversity, fertilizer is routinely applied in post mining restoration to enhance plant growth and establishment. Focusing on surface mine restoration (predominately bauxite and mineral sands), we outline the long-term negative impacts of fertilizer, particularly phosphorus fertilizer, on plant community composition, species richness, fire fuel loads, and belowground impacts on nutrient-cycling. We draw from extensive research in south-western Australia and further afield, noting the geographical coincidence of surface mining, phosphorus impoverished soil and high plant biodiversity. We highlight the trade-offs between rapid plant-growth under fertilisation and the longer-term effects on plant communities and diversity. We note that the initial growth benefits of fertilisation may not persist in water-limited environments: growth of unfertilised forests can eventually match that of fertilised forest, throwing doubt on the premise that fertilisation is necessary at all.